The association between dividend payout and firm growth: Australian evidence. (15th April 2018) - Dempsey, Michael; Gunasekarage, Abeyratna; Truong, Thanh Tan
Abstract: We report that whereas firms with high earnings distributions tend to have low‐to‐moderate growth (consistent with conventional theory), firms with low earnings distributions run the range between high and low performers. We interpret our findings for firm growth and payout policy in relation to the firm's location on the Boston Consulting Group (BCG) matrix that combines high/low growth with high/low market share. Our findings suggest that the market has difficulty in distinguishing between these types of firms. A concern is that investor preferences as an outcome may be focussed on dividend‐paying firms at the expense of younger growing firms in need of retained earnings.